Innovation and public policy - Goolsbee, Austan; Jones, Benjamin F. (National Bureau of Economic Research conference report., 2022)
Using the latest empirical and conceptual research for readers in economics, business, and policy, this volume surveys the key components of innovation policy and the social returns to innovation investment. In advanced economies like the United States, innovation has long been recognized as a central force for increasing economic prosperity and human welfare. Today, the US government promotes innovation through various mechanisms, including tax credits for private-sector research, grant support for basic and applied research, and institutions like the Small Business Innovation Research Program of the National Science Foundation. Drawing on the latest empirical and conceptual research, Innovation and Public Policy surveys the key components of innovation policy and the social returns to innovation investment. It examines mechanisms that can advance the pace of invention and innovative activity, including expanding the research workforce through schooling and immigration policy and funding basic research. It also considers scientific grant systems for funding basic research, including those at institutions like the National Institutes of Health and the National Science Foundation, and investigates the role of entrepreneurship policy and of other institutions that promote an environment conducive to scientific breakthroughs.